Bioinformatics and Expression Analysis of IDA-Like Genes Reveal Their Potential Functions in Flower Abscission and Stress Response in Tobacco (Nicotiana tabacum L.) - Guo, Cun; Wang, Qi; Li, Zhiyuan; Sun, Jinhao; Zhang, Zenglin; Li, Xiaoxu; Guo, Yongfeng (Frontiers in Genetics, 2021)
The INFLORESCENCE DEFICIENT IN ABSCISSION-Like (IDL) genes have been shown to play critical roles in floral organ abscission, lateral root formation and various stress responses in Arabidopsis. The IDL gene family has been characterized in a number of plant species, while limited information is available about IDL genes of tobacco. In the current study, 15 NtIDL members were identified in the tobacco genome, and were classified into six groups together with IDL members from other species. Evolution analysis suggested that the NtIDL members form group VI might have originated from duplication events. Notably, NtIDL06 shared high similarities with AtIDA in the EPIP sequence, and its encoding gene was highly expressed in the abscission zone of flowers at late developmental stages, implying that NtIDL06 might regulate tobacco flower abscission. In addition, the results from cis-elements analysis of promoters and expression after stress treatments suggested that NtIDL members might be involved in various stress responses of tobacco. The results from this study provide information for further functional analysis related to flower abscission and stress responses of NtIDL genes.